The dynamic behavior of the early dental caries lesion in caries‐active adults and implications. Issue 3 (5th February 2015) - Brown, John P.; Amaechi, Bennett T.; Bader, James D.; Shugars, Daniel; Vollmer, William M.; Chen, Chuhe; Gilbert, Gregg H.; Esterberg, Elisabeth J.; the X‐ACT Collaborative Research Group
Abstract Objective To describe the full range of behavior of the visible, noncavitated, early caries lesion in caries‐active adults with substantial fluoride exposure, and to consider implications. Methods The data were from the Xylitol for Adult Caries Trial (X‐ACT) collected annually for 33 months using condensed ICDAS caries threshold criteria. Individual tooth surfaces having a noncavitated caries lesion were included, and the patterns of transition to each subsequent annual clinical examination to sound, noncavitated or cavitated, filled or crowned were determined. The resulting sets of patterns for an individual tooth surface, looking forward from its first appearance as a noncavitated lesion, were combined into one of four behavior profiles classified as reversing, stable, oscillating, or continuously progressing, or were excluded if not part of the caries continuum. The distributions of profile types were assessed using the Rao–Scott chi‐square test, which adjusts for clustering of tooth surfaces within teeth. Results Inter‐ and intra‐examiner kappa scores demonstrated acceptable calibration at baseline and annually. 8084 tooth surfaces from 543 subjects were included. The distribution of profile types differed significantly between coronal and root surfaces. Overall, two‐thirds of all coronal noncavitated lesions were first seen at baseline, half reversed, over a fifth were stable, 15% oscillated, and only 8.3% progressed to cavitation, filled, or crowned in 33 months or less (6.3% consistently Progressed plus 2.0% inconsistently, a subset of oscillating, which oscillated before progressing to cavitation). Approximal, smooth, and occlusal coronal surfaces each were significantly different in their individual distributions of profile types. Xylitol showed no significant and consistent effect on this distribution by tooth surface type. This was in keeping with the X‐ACT's lack of effect of xylitol at the noncavitated plus cavitated lesion thresholds combined. Conclusions This study demonstrated the full dynamic range of early caries lesion behavior. The great majority were not progressive, and few (8.3%) became cavitated over 33 months in caries‐active adults using fluorides. Important caries management implications favoring recorded longitudinal monitoring, prevention of active risks, and minimal restoration only after direct visual determination of cavitation are discussed.